Respuesta :

Ax^2 + bx + c — this is your standard formula.

If a is greater than 1, you will want to multiply (a)x(c) next, you will find 2 numbers that multiplied together add up to the value of ac and added together are the value of c.

Next you will input those two numbers in for the value of b, and keep your x with both of the number.

Then you’ll want to factor by parts.


Example:

2x^2 + 7x + 6 = y

2(6) = 12. Two numbers that add up to 7 but multiplied equal to 12 are 4 and 3.

So then it will look like this:


2x^2 + 4x + 3x + 6 = 0

Then factor by parts

2x (x + 2) + 3 (x + 2) = 0

So then your values are

(x + 2)( 2x + 3) = 0

Then your x values are

X = -2
X = -3/2

Hope this helped!!
ACCESS MORE